Transcriptional regulation of the HMGA1 gene by octamer-binding proteins Oct-1 and Oct-2. - Eusebio Chiefari (Public Library of Science (PLoS), 2013)
The High-Mobility Group AT-Hook 1 (HMGA1) protein is an architectural transcription factor that binds to AT-rich sequences in the promoter region of DNA and functions as a specific cofactor for gene activation. Previously, we demonstrated that HMGA1 is a key regulator of the insulin receptor (INSR) gene and an important downstream target of the INSR signaling cascade. Moreover, from a pathogenic point of view, overexpression of HMGA1 has been associated with human cancer, whereas functional variants of the HMGA1 gene have been recently linked to type 2 diabetes mellitus and metabolic syndrome. However, despite of this biological and pathological relevance, the mechanisms that control HMGA1 gene expression remain unknown. In this study, to define the molecular mechanism(s) that regulate HMGA1 gene expression, the HMGA1 gene promoter was investigated by transient transfection of different cell lines, either before or after DNA and siRNA cotransfections. An octamer motif was identified as an important element of transcriptional regulation of this gene, the interaction of which with the octamer transcription factors Oct-1 and Oct-2 is crucial in modulating HMGA1 gene and protein expression. Additionally, we demonstrate that HMGA1 binds its own promoter and contributes to its transactivation by Oct-2 (but not Oct-1), supporting its role in an auto-regulatory circuit. Overall, our results provide insight into the transcriptional regulation of the HMGA1 gene, revealing a differential control exerted by both Oct-1 and Oct-2. Furthermore, they consistently support the hypothesis that a putative defect in Oct-1 and/or Oct-2, by affecting HMGA1 expression, may cause INSR dysfunction, leading to defects of the INSR signaling pathway.